Pengaruh POC Air Cucian Beras dan Media Tanam terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Dwi Prasetyo; Pramono Hadi; Srie Juli Rachmawatie (MAN 4 Kota Pekanbaru, 2026)
This study aimed to examine the effect of different growing media compositions and liquid organic fertilizer (POC) derived from rice washing water on the growth and yield of pakcoy (Brassica rapa L.). The experiment used a factorial Completely Randomized Design (CRD) with two factors. The first factor was the composition of growing media consisting of soil, rice husk charcoal, and goat manure with three ratios: M1 (1:1:2), M2 (2:1:1), and M3 (1:2:2). The second factor was liquid organic fertilizer from rice washing water applied at three concentrations: K1 (0%), K2 (15%), and K3 (30%). The results showed that the application of rice washing water POC at 15% concentration positively affected root length, while the growing media compositions significantly influenced leaf number, leaf width, consumption weight, and root length. The interaction between M1 and K3 produced the highest consumption weight (78.67 g), indicating that this combination was the most optimal for pakcoy growth and yield. In conclusion, the interaction between rice washing water POC and growing media significantly affected plant fresh weight, consumption weight, and root length.